Editor’s Note - Murunga, Godwin R. (Africa Development, 2023)
Preparation of this issue of Africa Development started under the direction of Prof. Ibrahim Oanda Ogachi while he served at the CODESRIA Secretariat in Dakar. Oanda, as we call him, was Senior Programme Officer in the Training, Grants and Fellowships (TGF) Programme and Acting Head of the Publication and Dissemination Programme. In August 2022, his contract with CODES- RIA came to an end. The Council retained his services under CODESRIA’s sabbatical arrangement until October 2022, when he formally resigned to join Mastercard Foundation as Head of Research Strengthening. A few of the forthcoming issues of CODESRIA journals, including Africa Development, Journal of Higher Education in Africa (JHEA) and CODESRIA Bulletin will still bear Prof. Oanda’s name as editor because he edited the manuscripts and over- saw the production of these articles before he left the service of the Council. Oanda, as he is popularly known at the Secretariat, first engaged with CODESRIA during the 1997 Democratic Governance Institute. Then a young lecturer at Kenyatta University, Nairobi, Kenya, he acquitted himself admirably at the Institute, whose director was the late Jean-Marc Ela. His first ever peer-reviewed publication was titled ‘Economic Reform, Political Liberalisation and Economic Ethnic Conflict in Kenya’, published in 1999 in Africa Development, Vol. 24, Nos 1&2 (10.4314/ad.v24i1.22118). Since then, Oanda has published on several platforms of intellectual engagement but especially in his area of expertise, the field of higher education stud- ies. His accomplished interventions in this field led him to be appointed one of the editors of the Journal of Higher Education in Africa and he con- tributed significantly to revitalising the journal to its current standing. He also scaled the heights of academia to become Associate Professor at Kenyatta University before he joined CODESRIA. At CODESRIA, Oanda served as Programme Officer in the Research Programme from June 2015 to August 2016, before being appointed by the Executive Committee to the position of Senior Programme Officer in TGF from September 2016 to 31 August 2022. Oanda revived several programmes at CODESRIA, including the higher education component of CODESRIA’s work and, briefly, the economic justice aspect of the Council’s programme. He was a key proponent of investing in what he justifiably understood to be CODESRIA’s core areas of work and in doing so he went the extra mile to secure funding to establish the Economic Justice Institute, which ran until 2017. While the initiative did not last, it remains a good illustration of Oanda’s belief that issues of economic justice ought always to be core to CODESRIA’s research agenda. Oanda stands out for his ability to raise funds for the Council. Over the period he worked at CODESRIA, he developed funding proposals to the Carnegie Corporation of New York, Andrew Mellon Foundation and Open Society Institute of Southern Africa (OSISA). By our internal calculations, he single-handedly raised USD 6,380,000. He also contributed to other funding proposals the Council developed, most importantly the proposed project on the Sahel. This project, developed jointly with the Arab Council for the Social Sciences, was meant to enable a reflection on the Sahel using the humanities as an entry point. Oanda developed and nurtured the Council’s relationship with funding partners and left a rich legacy of fundraising on behalf of the Council. Indeed, among CODESRIA’s senior programme staff he holds the record for fundraising, which he was focused on up to his last days at CODESRIA. To the last day, he remained concerned about the health of the Council especially in the context of the series of audits the Council went through after 2020. But perhaps Ibrahim Oanda’s greatest legacy to CODESRIA is its publish- ing system. By the end of 2019, the Council had accumulated a backlog in all its core journals, including Africa Development. I requested senior colleagues in the Secretariat to work together to resolve this challenge. Ibrahim Oanda agreed to step in as Acting Head of Publications and deal with the problem. Through a consultative process, he reorganised the different editorial and production elements of the programme, secured qualified and competent external service providers for copy-editing, cover design, typesetting, proof- reading and indexing, and put them to work. He created an editorial and production pipeline, set targets for staff and worked meticulously to reduce and eliminate the backlog. Oanda facilitated the development of a new database for peer review, created a systematic process of tracking articles and ensured that a proper system of feedback to researchers was established. He nudged the Council to invest in proper dissemination channels so that the work of the Council would be easily and effectively projected to the wider society and the impact of its research would be felt beyond the academy. He even fundraised for dissemination and ensured that modest resources were available in budgets to facilitate dissemination. A significant component of the recent advancements in CODESRIA’s communication and dissemination is in large measure due to Oanda’s effort. Once the publication system was running smoothly, CODESRIA was able to generate enough content to sustain a daily update to the community through our different platforms, including our website and social media. This was in no small measure due to the effort, commitment and hard work of Oanda. By the time he departed from the Council, both Africa Development and JHEA had a sufficient number of articles. He left behind enough fully edited and typeset articles to cover all the available issues of Africa Develop- ment for 2023. This is the reason his name will appear as editor of some of the forthcoming issues of Africa Development, even though he has formally left the Council. On behalf of the Executive Committee, staff of the Secretariat, and the community in general, I want to express our gratitude to Prof. Ibrahim Oanda Ogachi for his excellent service to CODESRIA and its community of schol- arship. His dedication to work, his commitment and loyalty to CODESRIA as an institution, and the humility with which he engaged with everyone, are all attributes worth emulating. As a Council, we wish him the very best in his new roles and look forward to reunion whenever opportunity allows.